Evaluación de la Influencia del Extracto Vegetal de Acelga (beta vulgaris var. cicla) en la Oxidación Lipídica durante el proceso de maduración del pepperoni. - Maliza Mendoza, Fabricio Leonardo (2019)
Currently, the synthetic antioxidants which cause diseases such as asthma and rhinitis are trying to be replaced partially or totally by natural antioxidants in food. These natural antioxidants help to slow down the aging of ripened raw meat products, also known as lipid oxidation, a process which produces unpleasant tastes and odors. That is why this research project had as aim to evaluate the influence of chard plant extract on lipid oxidation during the pepperoni ripening process by determining the amount of peroxides present in the different treatments evaluated during 28 days of maturation. An experimental design A x B + 1 was applied, obtaining 9 treatments plus a control, where factor A established the percentages of plant extract and factor B, the percentages of ascorbic acid. Ten treatments were formulated as indicated: control (0.33% nitrated salt and 0.14% ascorbic acid), T1 (0.25% vegetable extract and 0% ascorbic acid), T2 (0.25% of plant extract and ascorbic acid), T3 (0.25% of plant extract and 0.50% of ascorbic acid), T4 (0.35% of plant extract and 0% of ascorbic acid), T5 (0.35% of plant extract and 0.25 of ascorbic acid), T6 (0.35% of plant extract and 0.50% of ascorbic acid), T7 (0.45% of plant extract and 0% of ascorbic acid), T8 ( 0.45% vegetable extract and 0.25% ascorbic acid), T9 (0.45% vegetable extract and 0.50% ascorbic acid). The Tukey Test was performed to obtain the best treatment. T6 was determined as the best treatment for containing a lower peroxide index, lower pH and higher acidity percentage, showing significant results during the maturation process (p <0.05). Comparing with the control, the T6 peroxide index presented a value of 1.66 meq / kg, being a value less than 1.75 meq / kg of the control. The bromatological analyzes, presented amounts of protein with a value of 29.31% being within the level of acceptance (25%). The microbiological count of T6 showed values <10 cfu / g of Staphylococcus aureus that are within the acceptance levels that are 1.0x103 cfu / g. And 1.9x10 cfu / g Clostridium perfringes which are within the acceptance levels being 1.0x103 cfu / g. Finally, Salmonella was not detected. The useful life time was determined by the method of accelerated stability for a time of 8 days (estimated consumption time 3 months), during which time there were no organoleptic changes and the absence of pathogenic microorganisms was determined. Therefore, the chard plant extract in combination with ascorbic acid inhibits the lipid oxidation during the ripening time of pepperoni, by having low levels of peroxides vs. a pepperoni made with nitrated salts